SUBCLINICAL SIGNS OF VASCULAR LESIONS IN PATIENTS WITH CHRONIC PYELONEPHRITIS WITH HYPERTENSION AND THEIR PHARMACOLOGICAL CORRECTION - Лучко, О. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Investigated odds ratio of subclinical signs of vascular lesions [endothelin-1 - ET-1, endothelium dependent vasodilatation – EDVD, endothelium independent vasodilatation – EIVD, velocity of the pulse wave – VPW, cardio-ankle vascular index – CAVI, aortic stiffness index – ASI, thickness intima-media complex – TIMC] in 100 patients with Chronic Pyelonephritis (CPN) and Hypertension (HTN). Found that the progression of signs of vascular lesions correlates with decreased the glomerular filtration rate <90ml/min. The analysis of the dynamics of the resilient-elastic properties of the arteries and endothelial dysfunction (ED) in the application of basic therapy of CPN and HTN with the inclusion of natural and synthetic drugs Canephron H and Meldonium digidratum. Admission of Meldonium digidratum in combination with Canephron H consisting of basic therapy CPN and HTN can slow the progression of subclinical signs of vascular lesions.